2013
DOI: 10.1002/adma.201205178
|View full text |Cite
|
Sign up to set email alerts
|

Chirality and Chiroptical Effects in Plasmonic Nanostructures: Fundamentals, Recent Progress, and Outlook

Abstract: Strong chiroptical effects recently reported result from the interaction of light with chiral plasmonic nanostructures. Such nanostructures can be used to enhance the chiroptical response of chiral molecules and could also significantly increase the enantiomeric excess of direct asymmetric synthesis and catalysis. Moreover, in optical metamaterials, chirality leads to negative refractive index and all the promising applications thereof. In this Progress Report, we highlight four different strategies which have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
566
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 660 publications
(570 citation statements)
references
References 99 publications
4
566
0
Order By: Relevance
“…The effect commonly measured is circular dichroism (CD), the differential absorption of left and right circularly polarized light by chiral molecules and materials 3 . Unlike organic molecules, where the chiroptical effects are typically small at visible wavelengths, larger inorganic systems (roughly over ten nanometres to several hundreds of nanometres) may show stronger chiroptical effects [4][5][6] . Several mechanisms were suggested for induction of chiroptical phenomena in such systems (both metallic and semiconducting).…”
mentioning
confidence: 99%
“…The effect commonly measured is circular dichroism (CD), the differential absorption of left and right circularly polarized light by chiral molecules and materials 3 . Unlike organic molecules, where the chiroptical effects are typically small at visible wavelengths, larger inorganic systems (roughly over ten nanometres to several hundreds of nanometres) may show stronger chiroptical effects [4][5][6] . Several mechanisms were suggested for induction of chiroptical phenomena in such systems (both metallic and semiconducting).…”
mentioning
confidence: 99%
“…[6] It has been shown that plasmonic nanostructures forming 1D [7] elements, 2D metasurfaces, [8][9][10] and 3D metamaterials [11] can exhibit linear chiral response due to their own, intrinsic chirality. Also semiconductor nanostructures can exhibit chiral features.…”
mentioning
confidence: 99%
“…1,2 A number of methods have been designed to arrange nanoparticles (NPs) in chiral assemblies. 3,4,5,6,7 The amplification of optical effects by the inclusion of metallic NPs in chiral nematic LCs has recently been explored very actively, especially as the chiral organization of gold or silver NPs promises fascinating metamaterial behaviour. 8,9,10,11 Optical metamaterials capable of interacting with circularly polarized (CP) light, based on helical structures, are of considerable interest as CP light can be used e.g.…”
mentioning
confidence: 99%